Organizational Resilience and Its Influence on Work-Related Performance Among Healthcare Workers - Devita Eryani Putri; Enniq Mazayudha; Nur Mukarromah (Universitas Muhammadiyah Surabaya, 2025)
Organizational resilience has emerged as a critical factor in maintaining workforce functioning in complex healthcare environments. However, empirical evidence examining its relationship with multidimensional work-related performance remains limited. This study aimed to examine the association between organizational resilience and work-related performance among healthcare workers in a hospital setting. A cross-sectional study was conducted among 135 healthcare workers, including nurses, physicians, and administrative staff at PKU Muhammadiyah Hospital Surabaya. Organizational resilience was measured using the Organizational Resilience Questionnaire (ORQ), while work-related performance was assessed as a multidimensional construct encompassing job performance, productivity, work engagement, and job involvement. Data were analyzed using Pearson correlation to evaluate the strength and direction of the relationships. The findings showed that organizational resilience was positively associated with overall work-related performance (r = 0.538, p < 0.001). When examined across dimensions, organizational resilience demonstrated significant positive correlations with work engagement (r = 0.557, p < 0.001), job performance (r = 0.492, p < 0.001), productivity (r = 0.461, p < 0.001), and job involvement (r = 0.438, p < 0.001). Among these, work engagement exhibited the strongest association, indicating that resilient organizational environments may particularly enhance employees’ psychological involvement and motivation. These results suggest that organizational resilience contributes consistently to both behavioral and psychological aspects of workforce functioning. In conclusion, organizational resilience plays a significant role in improving work-related performance among healthcare workers. Strengthening resilience within healthcare organizations may serve as a strategic approach to enhancing workforce effectiveness and sustaining high-quality healthcare delivery.